Variable size of blocks for embedding watermark images using ISB technique - Zeki, Akram M.; A. Manaf, Azizah; Mahmod, Shayma'a S. (IEEE, 2016)
In Intermediate Significant Bits (ISB) model, the watermarking technique was shown to be made robust against different types of attacks with maintaining the quality of watermarked images. In addition, ISB model was found to work properly with many other techniques based on the Least Significant Bits (LSB). In this paper, two improvements approaches were suggested to make the system more robust, both approaches based on partitioning the host image into blocks. The first approach embeds the information based on the average of pixels values; while the second approach repeats the embedded information in a special form in order to improve the robustness. The two improvements processes were applied again and different sizes of blocks were done to further enhance robustness while keeping a high capacity. Most significant bits of watermark image should be embedded within the big size of blocks and the least significant bits of watermark image would be embedded within small size of blocks since most significant bits are more important for image quality than the least significant bits.